Difficulties predicting time-to-arrival in individuals with autism spectrum disorders - Sheppard, Elizabeth; van Loon, Editha; Underwood, Geoffrey; Ropar, Danielle (Elsevier, 2016)
Background: Previous research suggests people with ASD may have various difficulties in processing and interacting with motion in the environment. We investigated whether individuals with ASD have difficulty judging the location of moving objects in a driving context using a time-to-arrival task. Methods: Participants with and without ASD viewed scenes that simulated self-motion towards a junction, while another car approached on a side road. Scenes terminated prior to either car reaching the junction and participants were required to decide which car would reach the junction first. Results: Participants with ASD made fewer correct responses although this was only true when self-motion was on a straight road. Conclusions: This difficulty in judging the location of moving objects could contribute to difficulties people with ASD experience in learning to drive.